Estimation of the remaining useful life of hydro generators - BERNARDES JUNIOR, José Vitor (2021)
The monitoring of generators’ condition is very desirable for a reliable operation of a hydropower plant. Maintenance activities can be scheduled to avoid unexpected failures that can lead to months or years of machines stopped without generation. Studies indicate that stator insulation is the leading cause of generator failure. In this sense, the proposal methodology’s base is the monitorization of the actual health stage of the stator insulation system of hydro generators. Partial discharge tests in stator windings are applied to access the insulation condition. An algorithm to estimate the remaining useful life is the main contribution of this work. This estimation is based on both statistical evaluations of hydro generators and the stator insulation system’s actual condition. Accelerated aging tests in stator specimens with wide variables acquisition are performed to understand the aging process. The proposed algorithm is tested in simulated cases and real data from a thermal cycle test, which observed an insulation breakdown.